2013
DOI: 10.1159/000355562
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation in Treatment of Pharyngolaryngeal Dysfunctions

Abstract: Objective: Neuromuscular electrical stimulation (NMES) has been proposed in the treatment of laryngopharyngeal dysfunctions (dysphonia, dyspnoea, dysphagia) for more than 40 years. Several studies have investigated possible therapeutic effects. Some researchers described favourable results, whereas others did not find relevant benefits. This article aims to review available studies to give an overview regarding the current state of knowledge. Methods: We conducted a selective literature search using PubMed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 69 publications
(179 reference statements)
0
21
0
3
Order By: Relevance
“…Some studies sustain the positive effect of the swallowing rehabilitation by using NMES 10,13,20,[28][29][30][31][32] . Ludlow et al 28 , in a study conducted in 2007 on 11 patients with pharyngeal dysphagia of different etiologies, reported a decrease in aspiration phenomena and penetration after electrical stimulation, by measuring with videofluoroscopy the hyoid movement and the subglottic air column position.…”
Section: Pro and Cons Of Nmesmentioning
confidence: 91%
See 2 more Smart Citations
“…Some studies sustain the positive effect of the swallowing rehabilitation by using NMES 10,13,20,[28][29][30][31][32] . Ludlow et al 28 , in a study conducted in 2007 on 11 patients with pharyngeal dysphagia of different etiologies, reported a decrease in aspiration phenomena and penetration after electrical stimulation, by measuring with videofluoroscopy the hyoid movement and the subglottic air column position.…”
Section: Pro and Cons Of Nmesmentioning
confidence: 91%
“…There are also many studies presenting a negative effect of neuromuscular electrical stimulation or no significant difference between electrical stimulation therapy and traditional dysphagia treatment 13,[33][34][35][36][37] . Studying the effect of surface electrical stimulation in normal volunteers, with the placement of different electrodes, Humbert et al 33 concluded that surface stimulation "would not be an acceptable alternative to the more invasive intramuscular stimulation for enhancing the hyolaryngeal elevation in dysphagia".…”
Section: Pro and Cons Of Nmesmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of NMES on dysphagia is still a matter of debate. In a recent structured review of the literature, Miller et al [8] reported that NMES could be a valid adjunct in patients with dysphagia and in patients with vocal fold paresis and underlined the need for more empirical data in order to fully understand the benefit of NMES. Some authors, in fact, documented swallowing improvement after NMES treatment, while other studies reported no effect of NMES on swallowing ability [1].…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos têm demonstrado melhora na fisiologia da deglutição (FREED et al, 2001;BLUMENFELD et al, 2006;BOGAARDT et al, 2009) GALLAS et al, 2010;HUANG et al, 2010;XIA et al, 2011 MEARIN, 2009;FALSETTI et al, 2009;DANIELS et al, 2009;BINGJIE et al, 2010;PARK et al, 2010 Em uma revisão de literatura, Miller et al (2013) tiveram como objetivo revisar os benefícios da EENM no tratamento da disfonia, dispnéia e da disfagia para demonstrar uma visão geral do atual estado de conhecimento nesta área. (SOUZA et al, 2003).…”
Section: Introductionunclassified